2022
DOI: 10.3390/ijms23052770
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Secreted by Glioma Stem Cells Are Involved in Radiation Resistance and Glioma Progression

Abstract: Glioblastoma is the most aggressive brain tumour with short survival, partly due to resistance to conventional therapy. Glioma stem cells (GSC) are likely to be involved in treatment resistance, by releasing extracellular vesicles (EVs) containing specific molecular cargoes. Here, we studied the EVs secreted by glioma stem cells (GSC-EVs) and their effects on radiation resistance and glioma progression. EVs were isolated from 3 GSCs by serial centrifugation. NanoSight measurement, cryo-electron microscopy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…These receptor cells survived radiation exposure and could efficiently form colonies, significantly enhancing cell migration and invasion. Mechanistic findings indicated that GSC-EV and its specifically wrapped miRNAs might induce phenotypic changes in the recipient cells by activating the PTEN/Akt pathway [ 93 ]. In addition, it was also shown that recombinant SEVs (R-EXO) from homologous glioma cells could carry TMZ and dihydrotanshinone (DHT), can reverse drug resistance, and enhance focal targeted drug delivery, defined as R-EXO-TMZ/DHT (R-EXO-T/D).…”
Section: The Roles Of Texs In Chemoresistancementioning
confidence: 99%
See 3 more Smart Citations
“…These receptor cells survived radiation exposure and could efficiently form colonies, significantly enhancing cell migration and invasion. Mechanistic findings indicated that GSC-EV and its specifically wrapped miRNAs might induce phenotypic changes in the recipient cells by activating the PTEN/Akt pathway [ 93 ]. In addition, it was also shown that recombinant SEVs (R-EXO) from homologous glioma cells could carry TMZ and dihydrotanshinone (DHT), can reverse drug resistance, and enhance focal targeted drug delivery, defined as R-EXO-TMZ/DHT (R-EXO-T/D).…”
Section: The Roles Of Texs In Chemoresistancementioning
confidence: 99%
“…Exosome-derived circZNF652 is significantly up-day expressed in glioma cells and can be taken up by other glioma cells. The entry of circ-0001445 into glioma cells promotes glioma migration and invasion by regulating the miR-486-5p/SERPINE1 signaling axis and the epithelial–mesenchymal transition process [ 93 ].…”
Section: The Roles Of Texs In Invasion and Metastasismentioning
confidence: 99%
See 2 more Smart Citations
“…Intercellular communication between GBM and the tumor microenvironment is achieved via direct exchange through ion channels, transporters, gap junctions, and extracellular vesicles, as well as secretion of cytokines, chemokines, and neurotransmitters [ 40 ]. Extracellular vesicles can transport microRNA and proteins that remodel the microenvironment to promote tumor aggressiveness, stimulate angiogenesis, and promote resistance to therapy, including chemotherapeutics and radiation [ 46 ]. Moreover, specific GSC subtypes localizing to different niches are shown to produce distinct extracellular vesicles that contribute to intratumoral heterogeneity [ 47 ].…”
Section: Interactions With Tumor Microenvironmentmentioning
confidence: 99%